Association between 23 urinary VOC metabolites and cardiovascular disease among NHANES participants - Lubna A. Zar (20495582) (2025)
This paper reports on the association between urine concentrations of Volatile Organic Compounds (UVOCs) metabolites and Cardiovascular Diseases (CVDs). This cross-sectional study uses a sample of participants from the NHANES (2017–2020). We assessed the dose association of UVOCs with CVD by running multivariable logistic regression models at the second, third and fourth quartiles. Among 2,363 participants in the National Health and Nutrition Examination Survey (NHANES) who had complete UVOC and CVD disease data, 11.9% (N = 282) had at least one cardiovascular disease event. The UVOCs of Acrolein (aOR 2.26, 95%CI 1.24–4.12 p = 0.01), Acrylamide (aOR 1.81, 95%CI 1.20–2.73, p = 0.006), 1,3-Butadiene (aOR 2.06 95%CI 1.13–3.75, p = 0.019), Propylene oxide (2.12, 95%CI 1.22–3.70, p = 0.01) in quartile-4 were associated with higher odds of CVDs. At high concentrations, metabolites of Benzene, Acrolein, Acrylonitrile, 1,3-Butadiene, and Crotonaldehyde increase the odds of developing stroke. Other Information Published in: International Journal of Environmental Studies License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/00207233.2024.2444195